(untitled) (The Journal of Medicine, Humanity and Media, 2023)
The pandemic of Covid-19 has brought global health and development to a new crossroads. On the one hand, health has become a major theme of universal concern to the international community, on the other hand, global health and development requires global mobilization and coordinated responses from governments, civil societies, and other international agencies and individuals more than ever, thus highlighting the importance of global health communication. During the epidemic, Chinese government initiated to build a Global Community of Health for All, which not only expressed China’s standing points on the global fight against the epidemic, but also reflected China’s new directions for health diplomacy and participation in global global health governance in the new era. So it is important to fully understand the critical role of global health communication from western experience so as to better guide health communication research and practice in China in the new time.